Pemikiran Politik Islam dalam Moderasi Beragama - Khoirul Huda; Nur Madiah Harahap; Fadhiel Akbar Al-Azhari; Afri Wulan Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Religious moderation is one of the national priority programs. Religious moderation can be interpreted as an effort to moderate religious adherents, so that in understanding and practicing their religious teachings they are not trapped in two extreme poles of being too strict or too loose. This also concerns religious tolerance, which means respecting other people's beliefs and actions even though they are wrong in our view. And this is a new thing, namely the people as a civil society which in history has experienced creation and turned into resistance and activism. Various things happened in Islamic political thought, including the repositioning of NU and Muhammadiyah. The flow of Islamic politics in Indonesia has actually been structured around Pancasila which is the basis of the state administration system presented by the first vice president, namely Bung Hatta, containing five precepts or principles that are the foundation for the state and the entire Indonesian nation.